Intervención de la malla vial local en la ciudad de Bogotá por Sintrauniobras Bogota D.C. (2022)
The purpose as future engineers of the University of Antonio Nariño, is to allow interaction with the environment and put into practice the knowledge acquired during the entire training process and thus provide a good contribution to the country. Providing the services of assistant engineer for the company Sintrauniobras Bogotá D.C.; and contributing to the planning and quality of the current project, implemented in road maintenance in the city of Bogotá. The main objective of this project is to improve the technical and economic aspects that contribute to the development of the company. Effectively improving the quality of life, offering better designs, and thus be able to meet the needs of the community, economic and social.